PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI KAHOOT TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI 4 GERENENG TAHUN PELAJARAN 2025/2026 - Masja’atul Zariyah; Muh. Taufiq; Ahmad Yudi Saputra; Muhammad Sururuddi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effect of using Kahoot application-based learning media on student learning outcomes in the Indonesian Language subject for fifth- grade students at SD Negeri 4 Gereneng. The research employed a quantitative method with a one-group pretest-posttest design. The sample consisted of 20 students selected through simple random sampling. Data were collected through multiple-choice tests to measure learning outcomes and questionnaires to capture student responses. The results showed that the average pretest score was 45.75, which increased to 81 in the posttest, indicating a significant improvement in student achievement. Furthermore, 65% of students expressed positive responses toward the use of Kahoot, highlighting its role in creating a more engaging and interactive learning environment. Hypothesis testing using the t-test confirmed that the t-count was greater than the t-table for both learning outcomes (27.41 > 1.725) and student responses (11.84 > 1.725), with a significance level of 0.05. These findings demonstrate that Kahoot-based learning media has a significant impact on improving student learning outcomes and can serve as an effective alternative for teachers to integrate technology into classroom learning.